The impact of tire rubber powder contaminants on the physical properties of loess - Liu, Shaoli; Sun, Qiang; Ma, Pengda; Lv, Rui; Zhang, He; Nan, Jingjing (Frontiers in Environmental Science, 2025)
With the development of industry and the popularization of automobiles, a large number of tires are produced globally every year, and the tire rubber powder contaminants (TRPC) generated by the friction with the ground during the driving of automobiles. Then the TRPC settled into the soil through atmospheric circulation, causing soil pollution and altering the properties of arable land. This paper focused on the impact of TRPC on the physical properties of loess, dealing with the effect of TRPC on the electrical resistivity, thermal conductivity, and ultrasonic velocity of loess. Conclusion can be drawn as follows: (1) resistivity of loess increased with the increase of TRPC content; (2) thermal conductivity of loess decreased with the increase of TRPC content; (3) ultrasonic wave velocity of loess decreased with the increase of TRPC content; (4) soil resistivity decreased with the increase of water content, thermal conductivity of soil increased with the increase of water content, and ultrasonic wave velocity showed an increasing then decreasing trend with the increase of water content. This paper analyzed the reasons for the change in the physical properties of loess from two aspects: the inherent properties of TRPC and water, and the microstructure changes of loess due to the addition of TRPC and water. This research findings could provide valuable reference for pollutant treatment, agricultural irrigation, soil structure assessment, geological hazard early warning and to rise widespread social attention to TRPC-contaminated soil.